Corporate governance and firm performance during the Covid-19 pandemic - wang, siqi (2022)
This paper focuses on the relationship between corporate governance mechanisms and performance as a result of the Covid-19 outbreak. Corporate governance has been a widely researched area by scholars and there has been a steady flow of relevant research. There is no definitive structure for effective corporate governance mechanisms, as there are differences in the governance mechanisms that match the industry, country and characteristics of the company. While differences do exist, corporate governance mechanisms still focus on the board of directors, organisational structure and external regulatory mechanisms. However, with the outbreak of Covid-19, the global corporate governance environment has changed and this paper seeks to examine the effectiveness of governance mechanisms during the crisis by comparing the relationship between performance and governance mechanisms of FTSE100 UK companies before and after Covid-19.